Synthesis of 1,3,4-Oxadiazoles via Annulation of Hydrazides and Benzene-1,3,5-triyl Triformate under Metal-Free Conditions - Yin, Zhiping; Power, Dennis J.; Wang, Zechao; Stewart, Scott G.; Wu, Xiao-Feng (Synthesis, 2018)
A new and efficient method for the synthesis of 1,3,4-oxadiazoles via the annulation of hydrazides with benzene-1,3,5-triyl triformate (TFBen) under metal-free conditions is reported. A broad range of hydrazides were transformed into the corresponding 1,3,4-oxadiazoles in good yields with excellent functional group tolerance.
Keywords: heterocycles; cyclisation; green chemistry; carbonylation; formates